Determinants of The Intention in Becoming an Online Enterpreneur Among Online Distance Learning Students in Malaysia - Zahir Osman,; Zulhairi Zakariah ,; Ratna Khuzaimah Mohamad,; Liana Mohamad, (Universiti Malaysia Sabah, 2019)
This study is aiming to evaluate of entrepreneurial education, self-efficacy and social influence on attitude and direct effect of attitude on intention to become online entrepreneur among students in online distance learning (ODL) higher institutions in Malaysia. The Structural Equation Model (SEM) technique was employed to analyse the casual relationships among entrepreneurial education, self-efficacy, social influence, attitude and intention. Partial Least Square (PLS) procedure was used to analyse the developed model by assessing the data obtained from a questionnaire survey that produced 272 usable questionnaires. The results showed that entrepreneurial education, selfefficacy and social influence have a positive and significant influence on attitude and attitude has a positive and significant influence on intention among students in Malaysian ODL tertiary institutions. The results suggest that ODL institutions should give greater emphasis on strengthening entrepreneurial education, self-efficacy, social influence, attitude to ensure their ODL students have strong intention to become online entrepreneur.